2013
DOI: 10.3390/molecules18089833
|View full text |Cite
|
Sign up to set email alerts
|

ADIBO-Based “Click” Chemistry for Diagnostic Peptide Micro-Array Fabrication: Physicochemical and Assay Characteristics

Abstract: Several azide-derivatized and fluorescently-labeled peptides were immobilized on azadibenzocyclooctyne (ADIBO)-activated slide surfaces via a strain-promoted alkyne-azide cycloaddition (SPAAC) reaction revealing excellent immobilization kinetics, good spot homogeneities and reproducible fluorescence signal intensities. A myc-peptide micro-array immunoassay showed an antibody limit-of-detection (LOD) superior to a microtiter plate-based ELISA. Bovine serum albumin (BSA) and dextran covalently attached via "clic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Kuzmin et al described a fast methodology for the immobilization of biotin onto ADIBO‐coated glass substrates and subsequent avidin selective immobilization . Pfeifer and co‐workers used ADIBO‐based SPAAC reaction to construct a diagnostic peptide microarray for tumor auto‐antibody tests in cancer detection . In continuation of previous works, Orski et al functionalized the alkyne‐derived polymer brushes through click‐type cycloadditions with azido‐containing compounds by two mechanisms: a SPAAC with DIBO and ADIBO or a CuAAC to a propargyl group .…”
Section: Introductionmentioning
confidence: 99%
“…Kuzmin et al described a fast methodology for the immobilization of biotin onto ADIBO‐coated glass substrates and subsequent avidin selective immobilization . Pfeifer and co‐workers used ADIBO‐based SPAAC reaction to construct a diagnostic peptide microarray for tumor auto‐antibody tests in cancer detection . In continuation of previous works, Orski et al functionalized the alkyne‐derived polymer brushes through click‐type cycloadditions with azido‐containing compounds by two mechanisms: a SPAAC with DIBO and ADIBO or a CuAAC to a propargyl group .…”
Section: Introductionmentioning
confidence: 99%
“…Pfeifer and co‐workers described the use of copper‐free click reactions of ADIBO‐functionalized slides with azide‐derivatized biomolecules for the preparation of microarrays useful for sensitive immunological tests. In an initial work they exploited the SPAAC reaction to construct peptide microarrays for tumor auto‐antibody molecular diagnosis tests, with a sensitivity and specificity comparable to microtiter plate‐based ELISA tests . For that, glass slides were initially functionalized with (3‐glycidyloxypropyl)‐trimethoxysilane (GOPTS), which were next immersed in a solution of ADIBO amine, to obtain an ADIBO‐terminated surface.…”
Section: Strain‐promoted Azide‐alkyne and Other [2+3] Cycloadditionsmentioning
confidence: 99%
“…2), we demonstrated that immobilized dextran and bovine serum albumin (BSA) efficiently blocked a fluorophor-labeled immunoglobulin from binding to the array surface. [5] In another ambitious project named SupraDiag, we are developing a supramolecular biosensor to be directly inserted into a vein via a catheter in order to continuously monitor drug concentrations in blood. Aside of potential risks to patients, device longevity and functionality may be strongly impacted by non-specific adsorption of blood and tissue fluid proteins as well as cellular components onto the surface of the implanted sensor device.…”
Section: Universities Of Applied Sciencesmentioning
confidence: 99%